2022
DOI: 10.1037/cou0000621
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the progress of the process: Codevelopment of the therapeutic alliance with maltreated adolescents.

Abstract: We used a longitudinal actor–partner interdependence model to examine the codeveloping alliance in alliance empowerment therapy (AET; Escudero, 2013), a manualized team-based approach developed in Spain specifically for child welfare-involved youth. In this first evaluation of AET, we sampled 102 adolescents, 83% of whom had been removed from their homes due to abuse or neglect, and 40% of whom were in crisis at the time of referral. Before each session, clients rated their improvement-so-far; after each sessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 43 publications
1
8
1
Order By: Relevance
“…Attachment theory (Bowlby, 1988) highlights the importance of therapist responsiveness in building the working alliance and developing a secure attachment. Therefore, it is not surprising that therapist responsiveness was related to client improvement in Escudero et al’s (2022) study.…”
Section: Between-person Working Alliance Strengthmentioning
confidence: 75%
See 4 more Smart Citations
“…Attachment theory (Bowlby, 1988) highlights the importance of therapist responsiveness in building the working alliance and developing a secure attachment. Therefore, it is not surprising that therapist responsiveness was related to client improvement in Escudero et al’s (2022) study.…”
Section: Between-person Working Alliance Strengthmentioning
confidence: 75%
“…Escudero et al’s (2022) study suggested that different dynamics (actor and partner effects) are related to client outcome. The clients in Escudero et al’s (2022) study were adolescents who had recently been abused and neglected and the treatment specifically prioritized the working alliance as a corrective experience.…”
Section: Between-person Working Alliance Strengthmentioning
confidence: 99%
See 3 more Smart Citations